Pemberdayaan Lansia Melalui Usaha Ekonomi Produktif oleh Bina Keluarga Lansia (BKL) Mugi Waras di Kabupaten Sleman - Febriyati, Febriyati; Suyanto, Suyanto (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2017)
Susenas data in 2013 mentions 8.05% Indonesia population is elderly. The elderly are often seen as burdens in the community. It makes the depressed elderly in terms ofphysical, psychological, economic, and social. These problems require settlement by empowering the elderly. There are groups of elderly community (Bina Keluarga Lansia—BKL) Mugi Waras in Dusun Blendung, Sumbersari, Moyudan, Sleman. They sane elderly empowerment through doing productive economic ventures. They did the elderly empowerment through economic productive effort. The aims of this study is to examine the stages of empowerment and the results achieved by BKL Mugi Waras through a program of productive economic ventures. The research method used was qualitative. Sampling method was snowball sampling. The technique of datacollection through interview, observation, and documentation. The results of this research are (1) the stage of elderly empowerment there are; build awareness, identification of needs and the planning, selection and implementation of the alternative type of business activity, development of business, and evaluation of business achievement; (2) the result of the elderly is empowerment are the fulfillment of the daily needs of the elderly, the presence of contentment, and increasing the participation in BKL Mugi Waras’s activities.Data Susenas 2013 menyebutkan 8,05% penduduk Indonesia adalah lansia. Lansia sering dipandang sebagai beban dalam masyarakat. Hal tersebut membuat para lansia tertekan dari segi fisik, psikis, ekonomi, maupun sosial. Permasalahan ini memerlukan penyelesaian dengan pemberdayaan lansia. Di Dusun Blendung, Desa Sumbersari, Kec. Moyudan, Kab.Sleman terdapat kelompok Bina Keluarga Lansia (BKL) Mugi Waras yang melakukan pemberdayaan lansia melalui usaha ekonomi produktif. Tujuan dari penelitan ini adalah untuk mengkaji tahapan pemberdayaan dan hasil yang dicapai oleh BKL Mugi Waras melalui program usaha ekonomi produktif. Metode penelitian yang digunakan adalah kualitatif. Metode pengambilan sampel adalah snowball sampling. Teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi. Hasil dari penelitian ini adalah (1) tahapan pemberdayaan lansia ada 5, yakni penyadaran, identifikasi kebutuhan dan perencanaan, pemilihan alternatif jenis usaha, pelaksanaan kegiatan, pengembanga, serta evaluasi; (2) hasil dari pemberdayaan lansia adalah terpenuhinya kebutuhan sehari-hari lansia dari segi materi, adanya kepuasan batin, dan meningkatnya partisipasi lansia dalam kegiatan BKL Mugi Waras.